Experiential Marketing Model on Hotels Owned by Regional Government of South Sumatra Province - Maftuhah Nurrahmi (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
Purpose of this study was to analyze hotel marketing strategies carried out by hotel owned by the South Sumatra regional government. This study was designing an experiential marketing strategy for hotels owned by the South Sumatra regional government and designing an experiential marketing model for hotels owned by the South Sumatra regional government. Research stage was divided into 3 phases, that was: analyzing the marketing strategies that had been carried out so far, designing experiential marketing strategies and designing experiential marketing models for hotels owned by the South Sumatra regional government. This study was to design experiential marketing strategies and experiential marketing models that were suitable for marketing hotels owned by regional government of the South Sumatra Province so that they could compete with other hotels in South Sumatra. Survey method by distributing questionnaires to hotel customers owned by regional government of the South Sumatra Province. Results showed that the marketing strategy used hotels owned by the South Sumatra regional government was still simple, so it required experiential marketing strategies to increase the number of occupants, and from the experiential marketing model showed that brand image affected customer satisfaction and experiential marketing affected the value of experience, where customer satisfaction and the value of experience had influences customer loyalty.